1996
DOI: 10.1063/1.118145
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum arc discharges preceding high electron field emission from carbon films

Abstract: Field emission measurements on chemical vapor deposition diamond and laser ablated a-C films show an activation step after reaching a certain critical electric field. At this field a vacuum arc of some hundred ns duration initiates. While high current arcing leads to the evaporation of the spot surface melting, amorphization or cracking of the film is encountered for lower currents. In any case, much higher electron emission can be observed after this activation procedure due possibly to tip formation resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(18 citation statements)
references
References 0 publications
1
16
1
Order By: Relevance
“…These results are in good agreement with the observations of Groning et al, 9 Talin et al, 10 and Coll et al, 4 but differ from those obtained, for example, by Satyanarayana et al 8 However, the latter used the parallel-plate anode geometry in their experiments. This method has a drawback of ''picking up'' the hottest spot on the sample, and therefore, provides no reliable information about the average FE properties of the material over large surface areas.…”
supporting
confidence: 90%
“…These results are in good agreement with the observations of Groning et al, 9 Talin et al, 10 and Coll et al, 4 but differ from those obtained, for example, by Satyanarayana et al 8 However, the latter used the parallel-plate anode geometry in their experiments. This method has a drawback of ''picking up'' the hottest spot on the sample, and therefore, provides no reliable information about the average FE properties of the material over large surface areas.…”
supporting
confidence: 90%
“…From these characterizations it is revealed that in general these films are inhomogeneous in structure, nanocrystalline in nature and have a distribution of carbon clusters confined to a nanometer size range. Contrary to what would be expected from the microprotrusion model of EFE, 23 the relatively smoother surfaces give the lowest turn-on field. Though it is believed that small grain sizes produce similar field enhancement effects like the sharp protruding structures, as has been argued by Chen et al 43 and Rouse et al, 44 but in view of these small grain size values, it may also be presumed that there is a network of grain boundaries and a higher level of nondiamond carbon ͑sp 2 C͒ components, which can increase the conductivity and assist in lowering the threshold field.…”
Section: Resultscontrasting
confidence: 79%
“…In spite of the fact that the original work on electron field emission from diamond was motivated by the discovery of its negative electron affinity ͑NEA͒, 22 the ease of emission from many carbon materials suggests that the NEA is not a prerequisite and may be a bonus feature. Besides the existence of several propositions such as microprotrusion on the emitting surface, 23 electron injection into the diamond conduction band from cathode electrode, 24 surface termination, 25 depletion layers, 25 film thickness, 25 impurity elements and subbands, 26 and controlling the microstructure in terms of sp 2 -bonded carbon phase ͑sp 2 C͒ as here. 25 Because of the paucity of a single definite source of electron emission, it defies our understanding of the EFE mechanism since no clear consensus has been yet established and remains elusive and divergent.…”
Section: Investigations Of the Electron Field Emission Properties Andmentioning
confidence: 99%
“…By biasing the sample to a negative potential ͑Keithley 237͒ while keeping the grid at ground, electron field emission occurs and the energy of the electrons are measured with the hemispherical energy analyzer of the spectrometer. 27 All measurements were performed at a pressure below 10 Ϫ9 mbar. The sample can be rotated in an azimuthal as well as in a polar direction for x-ray photoelectron diffraction.…”
Section: Methodsmentioning
confidence: 99%